2018
DOI: 10.3389/fimmu.2018.01317
|View full text |Cite
|
Sign up to set email alerts
|

V(D)J Rearrangement Is Dispensable for Producing CDR-H3 Sequence Diversity in a Gene Converting Species

Abstract: An important characteristic of chickens is that the antibody repertoire is based on a single framework, with diversity found mainly in the CDRs of the light and heavy chain variable regions. Despite this apparent limitation in the antibody repertoire, high-affinity antibodies can be raised to a wide variety of targets, including those that are highly conserved. Transgenic chickens have previously been generated that express a humanized antibody repertoire, with a single framework that incorporates diversity by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Wu et al reported the fraction of cysteines out of the total amino acid content of CDR-H3 at 9.4% in wild-type chickens versus 1.6% in humans [12]. Because the V regions of the OmniChicken are entirely human, we rarely observe non-canonical cysteine residues [19]. In fact, deep sequencing of the antibody repertoire of a cohort of OmniChickens showed less than 1.5% cysteine content in CDR-H3.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Wu et al reported the fraction of cysteines out of the total amino acid content of CDR-H3 at 9.4% in wild-type chickens versus 1.6% in humans [12]. Because the V regions of the OmniChicken are entirely human, we rarely observe non-canonical cysteine residues [19]. In fact, deep sequencing of the antibody repertoire of a cohort of OmniChickens showed less than 1.5% cysteine content in CDR-H3.…”
Section: Discussionmentioning
confidence: 67%
“…Like our previously described Vκ insertion, all noncoding regions of the transgenes were chicken, including enhancer elements and promotor sequences. These Vλ-expressing chickens were then bred to birds with either a pre-rearranged human VH3-23 (SynVH-C) or rearranging VH3-23 (SynVH-SD) at the chicken heavy chain locus, both previously described [19], and combined with knockouts on the other allele for each locus, producing birds with the genotype SynVL/IgLKO; SynVH/IgHKO.…”
Section: Insertion Of Lambda Transgenementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the V H sequence inserted in the SynVH-C OmniChicken strain was derived from a human B cell library and is 86% identical to the closest human germline gene, V H 3-23, and the median identity of the V H s of anti-LAMP1 mAbs was similar. This result was expected considering the 97% human identity of the synthetic human pseudogenes inserted into this OmniChicken strain and the prevalent role of gene conversion in chicken [ 19 ]. No sequence donated by chicken pseudogenes was observed.…”
Section: Resultsmentioning
confidence: 80%